2014
DOI: 10.4018/jcit.2014040103
|View full text |Cite
|
Sign up to set email alerts
|

Flipped University Classrooms

Abstract: The three case studies in this paper show how flipped classroom approaches can facilitate the renewal of university teaching. The case studies form part of a scholarship of teaching and learning that provides opportunities for educators to learn from the experiences of others. Descriptions of course preparation illuminate the application of constructivist pedagogy, the affordances of a range of learning technologies, and a role for university teachers that facilitates their students' engagement with learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Chhabra & Sharma (2013) suggest that online communication may have some benefits in that introverted students are more likely to communicate ideas and there is less intimidation among students. The convenience factor also encourages student participation (Sankey & Hunt, 2014). Szewkis et al, (2011:564) recognized that "silent" online collaboration involves different group communicative dynamics than in person "spoken" collaboration.…”
Section: Technology: Group Sizementioning
confidence: 99%
“…Chhabra & Sharma (2013) suggest that online communication may have some benefits in that introverted students are more likely to communicate ideas and there is less intimidation among students. The convenience factor also encourages student participation (Sankey & Hunt, 2014). Szewkis et al, (2011:564) recognized that "silent" online collaboration involves different group communicative dynamics than in person "spoken" collaboration.…”
Section: Technology: Group Sizementioning
confidence: 99%
“…Over the past decade, there has been a great deal of attention placed on active and experiential learning. Specifically, researchers have focused on the flipped classroom and the use of games and technology to facilitate learning (Sankey and Hunt, 2014). Several authors have identified the value of using games with and without technology in the classroom (Bowen, 2012;Sheldon, 2011).…”
Section: Simulation Games In Academiamentioning
confidence: 99%
“…Halili and Zainuddin state that flipped classroom is an integrated learning element, integrating face-toface learning in the classroom through group discussion and distance learning outside the classroom with asynchronous learning and online collaboration [14]. In flipped classroom, teachers become trainers, more focused on becoming facilitators than teaching [9]. A model of flipped classroom can be like a teacher who gives students some reading in a training session and asks them to read at home.…”
Section: Introductionmentioning
confidence: 99%